Group breathing-based exercise to improve cardiopulmonory fitness of aged care patients in Werdha Wana Seraya Denpasar - Ni Made Parwati; I Nyoman Mangku Karmaya; Dewa Putu Sutjana (Universitas Udayana, 2013)
The aging process greatly impacts upon individual’s physical, mental, psychosocial and spiritual health. Those aged 30 years and over experience an annual 1% decline in cardiopulmonary fitness every year. Based on this, it is estimated that oxygen consumption capacity by cardiopulmonary fitness of someone aged 60 years will eventually decline to 35%. This study assessed the positive impact of breathing-based exercise on cardiopulmonary fitness of the aged patients of Werdha Wana Seraya in Denpasar. The aims of this study were to identify and to analyze differences of mean cardiopulmonary fitness among aged care patients before and after carrying out breathing-based exercise. Study design used one group pretest and posttest based on sample of 15 individuals using a purposive sampling. The cardiopulmonary fitness is measured using the Rockport method. The independent variable was breathing-based exercise and cardiopulmonary fitness was the dependent variable. Breathing-based exercise was held three times a week over a period of eight weeks during which time data on the impact on cardiopulmonary fitness were collected. Data were analysed using a paired sample t test. The study found that breathing-based exercise can improve cardiopulmonary fitness from 21 ml/kg/min up to 21.87 ml/kg/min [p=0.0001]. To conclude, conducting breathing-based exercise with aged cared patients can have a positive impact on their cardiopulmonary fitness and such activities should be supported.